سياسة التدخل الاقتصادي الغربي بعد نهاية حقبة الحرب الباردة - ميليش فريد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يناقش البحث قضية هامة ظهرت بعد نهاية الحرب الباردة 1990, والتي تحددت بموجبها صيغة العلاقات الدولية ، مع ظهور العولمة الاقتصادية, والتي رافقت المشروع الغربي للسيادة العالمية, عبر التدخل في دول ذات سيادة, باستخدام الأدوات والأساليب الاقتصادية, التي تحولت الى صيغ للهيمنة على العالم عامةً, والدول النامية خاصةً, لتكون شكل من أشكال العلاقات الإستعمارية التي تشبه الأنتداب, ما سيؤدي إلى نزاعات إقليمية ودولية, و ردود أفعالٍ, قد تصل حد إنهاء صيغة النظام العالمي القائم حالياً. The study discusses an important issue that emerged after the end of the Cold War in 1990, in which the formula of international relations was determined by the emergence of economic globalization, which accompanied the Western project of global sovereignty through interference in sovereign states using economic tools and methods that became formulas for world domination in general , And developing countries in particular, to form a form of colonial relations similar to the mandate, which will lead to regional and international disputes, and reactions, may end the termination of the existing global system.